Smart Co-housing for People With Disabilities: A Preliminary Assessment of Caregivers’ Interaction With the DOMHO System - Bacchin, Davide; Pluchino, Patrik; Grippaldi, Adriana Zoe; Mapelli, Daniela; Spagnolli, Anna; Zanella, Andrea; Gamberini, Luciano (Frontiers in Psychology, 2021)
Everyday millions of people with disabilities face a daily routine with obstacles to their independence and the accessibility of the spaces they live in, as these places often present insurmountable barriers. These individuals are typically older adults and people with motor or cognitive disabilities. The DOMHO project aims to find answers for these fundamental problems with an innovative solution: a smart home provided with a series of home automated and intelligent technologies. The apartment developed aims to host groups of three people with disabilities and an operator in a co-housing setting. Therefore, the present study analyzed the interaction of 7 operators with the system control application. They performed four tasks, analyzed with self-report tools (i.e., a questionnaire and an interview), computerized video analysis and performance measures. The video and performance analysis highlighted the characteristics of the interface to improve to develop a smoother, easier, and more enjoyable interaction. The interviews contributed with insights for designing Internet of Things (IoT) systems in the ambient assisted living field. Finally, the ad hoc questionnaire shows a general appreciation and trust in the system, also regarding privacy and sensitive data, which have always been among the main barriers in adopting IoT-based technologies. The expectation is that this study, and the DOMHO project, can lay the foundations for the user-centered design of systems capable of taking care of the person with disabilities, increasing their independence, breaking down architectural barriers and stimulating the social component to combat loneliness and social isolation.